PROVIDING BY BASIC DATA OF MATHEMATICAL HYDROGEOLOGYCAL MODELS AT THE DESIGN OF STREAMS OF THE GROUND WATERS ON THE URBANIZED TERRITORIES - KOSHLIAKOV, O.; DYNIAK, O.; KOSHLIAKOVA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The possibility and effectiveness of geographical information systems sapplied for geofiltrative schematization in mathematical modeling of waterlevel is considered. The construction of geofiltrative parameters grids is demonstrated in conditions of lack of inputdata in studying of waterlevel dynamics at urban territories.